Utilization of coconut fiber and corn cob waste as noise reducers - Amalia Ma'rifatul Maghfiroh; Ardana Putri Farahdiansari (University of Muhammadiyah Malang, 2023)
Noise is a very disturbing problem in residential, office, educational, industrial and other environments. Noise can be reduced by using materials that can dampen and absorb sound. The sound dampening materials that are widely used by the public generally use glasswool and rockwool, but they are expensive. The more expensive the price of goods including sound absorbers, the more alternatives are needed by utilizing materials derived from nature which are easy to obtain and cheaper, besides that by utilizing existing natural fibers it can also reduce waste in the surrounding community. One example of utilizing waste from natural fibers is making composites using coconut fiber and corn cobs. Composite materials made from coconut coir fiber and corn cob are alternative sound absorbing materials that are environmentally friendly, easily available and inexpensive. The aim of the research was to obtain an optimum composition ratio to produce composites as environmentally friendly sound absorbing materials, to determine the value of the sound absorption coefficient (α) from the manufacture of coco fiber and corn cob composites as noise dampening materials. From the research results it can be concluded that the sound dampening ability results show varying values ​​for each test specimen. The highest incoming sound/energy is 94.4 dB at a frequency of 500 Hz while the lowest incoming sound/energy is 44.14 dB at a frequency of 125 Hz. Meanwhile, the highest sound/absorbed energy (mean value) was 37.7 dB at a frequency of 750 Hz in sample C, while the lowest sound/absorbed energy was -6.16 dB at a frequency of 4000 Hz in sample A. Keywords: composites, noise, sound absorbing materials